MENJAGA KERUKUNAN: STRATEGI TOKOH AGAMA DAN ADAT DALAM MEMBANGUN HARMONI ISLAM-KRISTEN DI DESA GULILING - Heriady Heriady; Siti Ainun Qolby; Muh. Zar Algifary; Nur Halifah; Muflihul Munawir (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to examine the strategies of religious and traditional leaders in maintaining harmonious relations between Muslims and Christians in Guliling Village. Religious diversity living side by side at the local level requires a contextual approach so that potential conflicts can be avoided and social harmony is maintained. This study uses a qualitative approach with a case study design to gain an in-depth understanding of the social practices that shape interfaith harmony. Data collection was conducted through in-depth interviews with religious leaders, traditional leaders, and the community, accompanied by direct observation and review of supporting documents. The results of the study show that harmony in Guliling Village develops through a process involving local cultural values, social closeness, and the example set by community leaders. social relations. This study contributes to the development Religious figures play a role in instilling values of tolerance and mutual respect through religious guidance, while customary leaders strengthen social harmony by preserving local wisdom that emphasizes interfaith brotherhood. Tolerance is manifested in everyday practices, such as respecting the implementation of worship, observing dietary boundaries, and participating in joint social activities. These findings affirm that harmony among religious communities is stronger when built through cultural approaches and sustainable of studies on interfaith harmony based on local wisdom in multicultural societies.